2008
DOI: 10.2139/ssrn.1145687
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Educational Investments in Children in the Developing World

Abstract: We bring together 40 randomized and non-randomized evaluations of education programs to compare cost-effectiveness, seeking to facilitate prioritization of different candidate interventions by policymakers. We examine cost-effectiveness across three outcomes (enrollment, attendance, and test scores) and find distinct "best interventions" for each outcome. For increasing enrollment, urban fellowships, school consolidation, and extra teachers have proven most cost effective. For school attendance, school-based d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…These are in the lower range of similarly-calculated cost-effectiveness ratios for interventions aimed at increasing enrollment (Evans and Ghosh, 2008). We also find substantial heterogeneity by the stratifying variable of mean municipal height-for-age, with full-sample effects accounted for by municipalities in the 2 poorest experimental blocks.…”
Section: Discussionmentioning
confidence: 59%
“…These are in the lower range of similarly-calculated cost-effectiveness ratios for interventions aimed at increasing enrollment (Evans and Ghosh, 2008). We also find substantial heterogeneity by the stratifying variable of mean municipal height-for-age, with full-sample effects accounted for by municipalities in the 2 poorest experimental blocks.…”
Section: Discussionmentioning
confidence: 59%
“…1 Mass deworming of children has been described as the most cost-effective strategy to improve educational attendance in endemic helminth countries. 2 Although deworming is inexpensive (US$0•50) per child, 3 the global cost of implementing the WHO recom mendations for all children is estimated to be $276 million annually. 4 A 2015 Cochrane review 5 concluded that mass deworming does not improve child health or school performance; however, concerns have been raised that the review did not sufficiently address a number of methodological issues that might have influenced its conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the successes of these initiatives have been 33 While this compares favourably to other interventions, such as those surveyed in Evans and Ghosh (2008), these effects are not directly comparable as they focus mostly on inschool interventions. Moreover, there is a trade-off between the more immediate returns on interventions targeted towards adults versus the shorter duration during which they accrue (due to the shorter remaining life expectancy).…”
Section: Resultsmentioning
confidence: 97%